Effect of reading clinic on scholastic success - Dye, Rachel F., author; Miller, Carroll H. (Carroll Hiram), 1907-, advisor; Durrell, L. W. (Lawrence Wood), 1888-1970, committee member; Canada, Ralph W., committee member; McClanahan, Walter R., committee member; Stinson, Dean, committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Reading -- Remedial teaching